2021
DOI: 10.3390/ani11102878
|View full text |Cite
|
Sign up to set email alerts
|

Rational Pharmacotherapy in Infectious Diseases: Issues Related to Drug Residues in Edible Animal Tissues

Abstract: Drugs are used in veterinary medicine to prevent or treat animal diseases. When rationally administered to livestock following Good Veterinary Practices (GVP), they greatly contribute to improving the production of food of animal origin. Since humans can be exposed chronically to veterinary drugs through the diet, residues in food are evaluated for effects following chronic exposures. Parameters such as an acceptable daily intake (ADI), the no-observed-adverse-effect level (NOAEL), maximum residue limits (MRLs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 180 publications
0
12
0
Order By: Relevance
“…A 6-month release period from a long-lasting ivermectin formulation may indeed lead to qualitatively and quantitatively different accumulation of the compound that could necessitate increased withdrawal time when compared, for example, to the recommended 28 days for classical products for cattle [ 53 ]. This should be characterized by taking into account the recommendations and frameworks of the Joint Food and Agriculture Organization (FAO)/WHO Expert Committee on Food Additives (JECFA, [ 54 , 55 ]). Basically, gestating and lactating females and animals intended for human or animal meat or milk consumption during the ivermectin releasing period should not be considered, unless owners' will and non-consumption guarantees are given.…”
Section: Discussionmentioning
confidence: 99%
“…A 6-month release period from a long-lasting ivermectin formulation may indeed lead to qualitatively and quantitatively different accumulation of the compound that could necessitate increased withdrawal time when compared, for example, to the recommended 28 days for classical products for cattle [ 53 ]. This should be characterized by taking into account the recommendations and frameworks of the Joint Food and Agriculture Organization (FAO)/WHO Expert Committee on Food Additives (JECFA, [ 54 , 55 ]). Basically, gestating and lactating females and animals intended for human or animal meat or milk consumption during the ivermectin releasing period should not be considered, unless owners' will and non-consumption guarantees are given.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics are administered to food-producing animals for several purposes, including therapeutic, metaphylactic, and prophylactic use, but they are also used as growth promoters. The latter involves administering low doses (sub-therapeutic) of antibiotics in feed or water over an extended period of time to improve growth and production efficiency [ 77 ]. Despite being prohibited as growth promoters in most countries, antibiotics are still used extensively for this purpose in certain regions/countries, including India and China [ 78 , 79 ].…”
Section: Antibiotics In Veterinary Medicine: Responsible and Prudent Usementioning
confidence: 99%
“…Concerning Europe, the trend highlighted by Tiseo et al [ 82 ] was confirmed by the efforts made to decrease the use of antibiotics through the European Union’s “Farm to Fork Strategy,” which aims for a 50% reduction in antimicrobial sales for farmed animals and aquaculture by 2030 [ 77 , 83 ].…”
Section: Antibiotics In Veterinary Medicine: Responsible and Prudent Usementioning
confidence: 99%
See 1 more Smart Citation
“…For each antimicrobial, the dosage and the recommended withdrawal period depend on the veterinary drug used and on the target species. However, residues of these compounds may remain in the animal food products if these drugs are incorrectly used or if recommended drug withdrawal periods are not observed [ 7 , 8 , 9 ]. The Commission Regulation (EU) N° 37/2010 of 22 December 2009 sets the maximum residue limits (MRLs) of veterinary drugs in foodstuffs of animal origin of 100 µg.kg −1 of meat for sulfonamides and tetracyclines [ 10 ].…”
Section: Introductionmentioning
confidence: 99%